Investigation of neurovascular coupling by synchronous EEG and fNIRS measurements during steady-state visual stimuli - Özker, Müge. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2009., 2009)
In this thesis, the steady state human visual evoked potentials that are generated in response to visual stimulation and its corresponding hemodynamic response are investigated via electroencephalography (EEG) and functional near infrared spectroscopy (fNIRS). The ssVEPs are investigated for the frontal and the occipital cortex and the corresponding HBO2 changes are investigated for the frontal cortex. The left and the right hemispheres are compared as well as the frontal and the occipital cortecies in terms of electrical activity and the hemodynamic response. The stimulus locked ssVEPs are time averaged in order to increase the signal to noise ratio and the power of the resulting averaged signals are calculated. On the other hand the mean values of the band passed ltered HBO2 signal for the stimulation intervals are calculated. The responses obtained from the frontal electrodes and fNIRS channels are averaged as well as the responses obtained from the occipital electrodes in order to see the overall electrophysiological and hemodynamic responses of the frontal and the occipital regions since the lateral response di erences turned out to be statistically insigni cant. The overall average calculated between the 13 subjects revealed that the ssVEP power observed for the frontal electrodes peak at the upper alpha band (10-13 Hz), and the ssVEP power peaks at 9 Hz frequency for the occipital electrodes, whereas the maximum hemodynamic response is observed at 24 Hz stimulation frequency. The correlation of the ssVEP and the hemodynamic responses obtained from the frontal cortex are analyzed. At 9, 12 and 20 Hz stimulation frequencies, the linear relationship between the ssVEP and the hemodynamic responses is determined to be positive and moderate. At 28 and 30 Hz stimulation frequencies a negative, moderate correlation is found between the ssVEP and the hemodynamic responses. Since, the maximal frontal ssVEP power and a moderate correlation between the ssVEP and the hemodynamic responses are both observed during 12 Hz visual stimulation, 12 Hz is assumed to elicit a strong neurovascular coupling in the frontal cortex.
Keywords: Near infrared spectroscopy.; Visual evoked response.; Electroencephalography.; Hemodynamics.; Prefrontal cortex.